Analysis of Return on Investment with the Du Pont System model : Case Study at PT. Mayora Indah Tbk., Period 2016-2020: Analysis of Return on Investment with the Du Pont System model - Sun Dewi Putri; Muhammad Ichwan Musa; Anwar Anwar (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
The purpose of this study is to find out the rate of return on investment in PT. Mayora Indah Tbk. PT. Mayora Indah Tbk., is a manufacturing company engaged in food and beverages and at the same time the largest coffee candy manufacturing company in the world. The analysis of the rate of return on investment in this study was measured using the Return On Investment analysis with the Du Pont System approach. The data collection method is carried out by documentation techniques using industry average assessment indicators from all companies such as research objects, namely in the form of food and beverage sub-sector manufacturing companies. The findings in this study show that the Return On Investment in PT. PT. Mayora Indah Tbk., for 5 years, namely 2016-2020, is in good condition because it is above the industry average. The findings in this study can help investors to invest in a company, it can be seen from how.